2011
DOI: 10.1016/j.febslet.2011.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase activity of the intracellular microcrystal of the firefly squid,Watasenia scintillans

Abstract: a b s t r a c tThe arm light organ of the firefly squid, Watasenia scintillans, emits extremely bright flashes of light, which are caused by a luciferin-luciferase reaction involving ATP, Mg 2+ and molecular oxygen. The molecular mechanism underlying the bioluminescence reaction has remained unresolved, because the luciferase could not be identified or isolated. The arm light organ contains numerous rod-like bodies that are 2-6 lm long and 1-2 lm thick. This paper addresses the characterization of the extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…In 2011, Hamanaka et al . confirmed that the rod-shaped objects are protein crystals, and demonstrated that they are the source of light production in the squid arm tip photophores12. This is the only report of naturally occurring protein crystals that are able to catalyse a bioluminescent reaction.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…In 2011, Hamanaka et al . confirmed that the rod-shaped objects are protein crystals, and demonstrated that they are the source of light production in the squid arm tip photophores12. This is the only report of naturally occurring protein crystals that are able to catalyse a bioluminescent reaction.…”
supporting
confidence: 58%
“…Both samples clearly showed two bands of approximately 59 and 81 kDa, assumed to be equivalent to the bands observed by Hamanaka et al . (approximately 63 and 81 kDa), where the crystals were purified using sucrose gradient centrifugation12. Whereas Hamanaka et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The firefly squid Watasenia scintillans emits intense blue bioluminescence from photophores located at the tip of two of its arms. Within the photophore, luciferases are specifically organised in microcrystals, and these proteins are catalysing the bioluminescent reaction using the coelenterazine disulfate luciferin and ATP (Hamanaka et al, 2011;Tsuji et al, 1985). The involvement of ATP in the luminescence reaction was however questioned (Teranishi and Shimomura 2008;Shimomura 2012).…”
Section: Fungi Luciferases (Group Iii) a Common Type Of Luciferase For All Fungimentioning
confidence: 99%